2014
DOI: 10.1007/s11249-014-0425-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interfacial Bonding on Friction and Wear at Silica/Silica Interfaces

Abstract: Static friction between amorphous silica surfaces with a varying number of interfacial siloxane (Si-O-Si) bridges was studied using molecular dynamic simulations. Static friction was found to increase linearly with the applied normal pressure, which can be explained in the framework of Prandlt-Tomlinson's model. Friction force was found to increase with concentration of siloxane bridges, but with a decreasing gradient, with the latter being due to interactions between neighboring siloxane bridges. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 40 publications
11
74
0
1
Order By: Relevance
“…Time-dependent formation of siloxane (Si-O-Si) bonds between a pair of opposing hydrolyzed silica groups (Si-OH) has been shown via atomic force microscopy to be a viable mechanism of frictional aging for nanoscale single-asperity silica-silica contacts (Li et al, 2011). Molecular simulations confirm the atomic force microscopy results and show that the number of siloxane bonds across a silica-silica interface increases linearly with the logarithm of contact time for an elastic contact (Li et al, 2014;Liu & Szlufarska, 2012). Thus, strong frictional aging occurs even in the absence of plastic deformation.…”
Section: Discussionmentioning
confidence: 82%
“…Time-dependent formation of siloxane (Si-O-Si) bonds between a pair of opposing hydrolyzed silica groups (Si-OH) has been shown via atomic force microscopy to be a viable mechanism of frictional aging for nanoscale single-asperity silica-silica contacts (Li et al, 2011). Molecular simulations confirm the atomic force microscopy results and show that the number of siloxane bonds across a silica-silica interface increases linearly with the logarithm of contact time for an elastic contact (Li et al, 2014;Liu & Szlufarska, 2012). Thus, strong frictional aging occurs even in the absence of plastic deformation.…”
Section: Discussionmentioning
confidence: 82%
“…In our experiments we used temperature-dependent friction force microscopy [28] to measure the lateral forces at the interface between an AFM cantilever covered by SiO 2 and p-type (111) Si wafers with either a native oxide layer or a 300-nm oxide layer. Since humidity is known to have a strong influence on microscopic and macroscopic contact aging [12,13,29], all experiments were conducted under ultrahigh vacuum conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The complexity of the process can be best understood starting from the idea that virtually any macroscopic surface exhibits a significant roughness, leading to a certain number of true contact points at the interface [10,11]. The dynamics of the junctions is then governed by a broad range of complex physical-chemical processes including bond formation [12][13][14][15][16], plastic flow [17], capillarity [18,19], and atomic attrition [20]. Through the time-dependent nature of these processes the contact strength is expected to increase logarithmically with time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first-principles calculations indicated that covalent interfacial siloxane (Si-O-Si) bridges are formed at silica-silica interfaces [61,64]. FFM measurements of single-asperity silica-silica nanocontacts [30] found that two metastable states are involved in the process of formation and rupture of Si-O-Si bridges, which are the dangling state (Si-O-) and passivated state (Si-OH).…”
Section: Two-state Distributionmentioning
confidence: 99%